A large focus of naturally acquired Plasmodium knowlesi infections in human beings - Singh, Balbir; Sung, L.K.; Matusop, A.; Radhakrishnan, A.; Shamsul, S.S.G; Cox-Singh, J.; Thomas, A.; Conway, D.J (The Lancet, 2004)
Balbir Singh, Lee Kim Sung, Asmad Matusop, Anand Radhakrishnan, Sunita SG Shamsul, Janet Cox-Singh, Alan Thomas, David J Conway UNIMAS